2008
DOI: 10.1002/adma.200702012
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Transitions in Thermotropic Liquid Crystals Induced by the Interfacial Assembly and Enzymatic Processing of Oligopeptide Amphiphiles

Abstract: A method leading to the preparation of oligopeptide‐decorated interfaces of liquid crystals is presented. The formation of the oligopeptide‐modified interface of the liquid crystal is accompanied by an orientational transition of the liquid crystal, and thus can be visually followed. Processing of the oligopeptide by an enzyme also results in an orientational transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
99
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 44 publications
2
99
0
Order By: Relevance
“…24,25 They showed that covalent attachment of the oligopeptide to the NHS-activated carboxylic acid groups of the lipid-laden monolayer led to an ordering transition in the LC; in addition, they demonstrated that the orientation of the LC at this interface could be selectively manipulated by contacting the oligopeptide-decorated LC with an enzyme that can cleave the immobilized oligopeptides. 24,25 This study was conducted to test the possibility of using this method as a general enzyme assay. The approach used in this study builds from the results of an experimental system that provides approximately planar and stable interfaces between aqueous phases and the LCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 They showed that covalent attachment of the oligopeptide to the NHS-activated carboxylic acid groups of the lipid-laden monolayer led to an ordering transition in the LC; in addition, they demonstrated that the orientation of the LC at this interface could be selectively manipulated by contacting the oligopeptide-decorated LC with an enzyme that can cleave the immobilized oligopeptides. 24,25 This study was conducted to test the possibility of using this method as a general enzyme assay. The approach used in this study builds from the results of an experimental system that provides approximately planar and stable interfaces between aqueous phases and the LCs.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al previously confirmed the successful conjugation of the oligopeptide to NHS-activated carboxylic acid groups presented at this interface using polarized modulation infrared reflection-adsorption spectroscopy (PM-IRRAS). 25 We used α-chymotrypsin as a model enzyme that can slice the oligopetide at four different locations. We found that α-chymotrypsin selectively cleaved peptide bonds after phenylananine (F) and tyrosine (Y) on the C-terminal side in the 17 amino-acid oligopeptide.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The biological activity involved in combining phospholipids was demonstrated to trigger orientational transition of LCs that can be readily visualized under crossed polarizers. [18][19][20] This coupling provides the foundation for transduction and amplification of biological events that occur at these interfaces. To the best of our knowledge, most previously reported research has focused on the secondary oxidation products or decomposition products of phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Due to its highly cooperative and long-range anchoring transitions, which propagate from aqueous/LC interfaces, LCs can be used to amplify and transduce molecular and biomolecular events into optical outputs visible by the naked eye. [13][14][15] Studies on highly sensitive LC-based biosensors based on the orientational transition of LCs involve pH indication, 16 enzymatic reactions, [16][17][18] DNA hybridation 19 and protein binding events. 20 In terms of pH sensors, amphiphiles containing pH-sensitive functional groups are usually employed to detect pH shifts related to ordering transitions of LCs.…”
Section: Introductionmentioning
confidence: 99%